POWER CAPACITY ASSESSMENT MANUAL OF MAGISTRATES/SERVERS REGIONAL LABOUR COURT OF REGION 19th ALAGOAS PARTICIPANTS OF GYMNASTICS CLASSES LABOUR (Fiep Bulletin - online, 2013)
The Gymnastics began to be understood as a major tool in improving the physical health of the employee reducing and preventing occupational problems. For (HARTMANN et al, 2008). The Regional Labor Court of Alagoas 19th Region concerned about the welfare of mankind in all its aspects, seeks to provide response mechanisms to prevent and minimize the consequences of various postural defects, injuries, occupational repetitive strain (RSI), structures that are degenerative and cumulative preceded by any pain or discomfort and even work-related disorders (MSDs), since we are aware that the body can not be separated from the mind, as it will only be complete and in full harmony, if running perfectly as a whole, in a single unit. Objective: This study aimed to evaluate the ability of manual force of magistrates / servers of the Regional Labor Court of the 19th Region Alagoas participating in gymnastics classes. Methodology: The sample consisted of 159 magistrates / servers males aged 21-61 years (X = 42.30 years), and 148 magistrates/servers females aged 20 to 64 years (X = 41.60 years) of the Regional Labor Court of the 19th Region Alagoas. For data collection was carried out test dynamometer adjusted to accommodate comfortably the anatomical individuality of the hands, and the server remained in a standing position, with the arm extended, as directed by the protocol Heyward & Franks (2000). Conclusion: After analyzing the results of the assessment of handgrip servers Regional Labor Court of the 19th Region Alagoas, we can verify that they are well below the capacity of force manual shows how the criterion of Heyward. We suggest that in gymnastics classes are used rubber balls, tennis balls and rubber garroche, so you can improve the strength of manual servers Regional Labor Court of the 19th Alagoas region.
Keywords: Gymnastics; Power Capacity; Manual Hold